Development of Conceptual Scaffolding-Assisted Formative Assessment for Enhancing Understanding of Temperature and Heat - Fitriyah, Ana Lailatul; Kusairi, Sentot; Diantoro, Markus (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2024)
This research aims to develop formative assessment media assisted by conceptual scaffolding to improve students’ understanding of temperature and heat, test its validity and practicality, and gauge student responses. Utilizing the ADDIE model, the research follows five stages: Analysis, Design, Development, Implementation, and Evaluation. In the Analysis stage, a literature review was conducted to identify critical components, including formative assessment, conceptual scaffolding, concept mastery, and previous research. The Design stage involved identifying users, defining competencies and indicators, creating a storyboard, integrating assessment components, and determining mastery levels. During the Development stage, the assessment media were developed into a functional product. The Implementation stage saw the validated assessment applied in classroom settings. In the Evaluation stage, feedback was used to refine the product. The assessment media is designed for use on Android devices and computers, available as a .apk file or via a website. Formative assessments evaluate student understanding by providing feedback and conceptual scaffolding, especially when students struggle with questions. Feedback and scaffolding prompts appear after incorrect answers, guiding students through conceptual questions in stages to build understanding. Students who correctly interpret the feedback demonstrate mastery of the concepts. The study’s findings reveal that the formative assessment media, assisted by conceptual scaffolding, is both valid (89%) and practical (80%) for teaching temperature and heat in physics.DOI: 10.17977/jps.v12i42024p123